STRUCTURAL STUDY ON THE DRAMA SCRIPT "LAUTAN BERNYANYI" BY PUTU WIJAYA - Syifa Nurlatifah; Resha Zakiyatussolihah; Jodi Iskandar; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to obtain a description of the elements that make up a drama script. The method used in the structural study of the drama script "Lautan Bernyanyi" by Putu Wijaya is to use a qualitative descriptive method. "Qualitative research is research used to examine the condition of natural objects. The data analysis technique used in this research is qualitative descriptive data analysis, namely describing the intrinsic elements contained in the drama script "Lautan Bernyanyi". The results of the research reveal that the plot of the drama script "Lautan Bernyanyi" by Putu Wijaya is classified as an advanced plot. The characters in the drama script "Lautan Bernyanyi" by Putu Wijaya consist of the characters Captain, Chomol, Panieka, Adenan, Rubi, Dayu Sanur, Shaman. The drama script "The Singing Ocean" is set on the deck of the Tiger Laut ship. The setting of Putu Wijaya's "Singing Ocean" takes place in an atmosphere of tension, anxiety, panic, fear, anger and joy. The major theme of the drama The Singing Sea is Captain Leo's doubts as a human being who always thinks logically and opposes forms of myth that have been passed down from generation to generation to be believed. The minor theme of the drama The Singing Sea is the relationship between Captain Leo and his subordinate Comol. The message can be taken, that we humans must have firm beliefs to determine something.